EFEKTIFITAS KEBIJAKAN PEMBERIAN TUNJANGAN KINERJA TERHADAP PENINGKATAN DISIPLIN PEGAWAI DI LINGKUNGAN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA (STUDI KASUS DI LAPAS NARKOTIKA KELAS IIA BANGLI) - Rusmantara, I Wayan; Rahmat, Diding (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
Class IIA Bangli Narcotics Penitentiary is a Technical Implementation Unit under the Ministry of Law and Human Rights of the Republic of Indonesia which is specifically designed to accommodate leukemia with drug conversion cases, in addition to functioning as a remote place, Class IIA Bangli Narcotics Penitentiary is also used as a Rehabilitation place for drug addicts. Therefore, agreeing to a very important thing, the government provides additional income called a performance allowance. The government hopes that with the existence of employee performance allowances, it can improve each person's self-discipline which will directly improve individual performance and the performance of the Class IIA Bangli Narcotics Penitentiary Technical Implementation Unit. This study aims to determine the Effectiveness of the Policy of Providing Performance Allowances on Improving Employee Discipline in the Ministry of Law and Human Rights (Case Study at Class IIA Bangli Narcotics Penitentiary). This study uses an empirical method with a factual approach or what is familiarly known as a factual approach in the field in the form of data collection such as laws and regulations, reports, Attendance and submission of performance permits and interviews. Data processing is carried out by looking at employee discipline that uses laws and regulations as a reference for employee behavior and using data in the form of absences, submission of performance allowances and data from interviews conducted with task and function holders in the personnel field to describe how effective the influence of the Performance Allowance Policy is on Improving Employee Discipline in the Ministry of Law and Human Rights. The results of the study show that the performance allowance policy has a positive impact on the quality of work, communication, and employee discipline. The quality of employee work is reflected in the low level of lateness and the achievement of the Corruption-Free Area (WBK) predicate in 2024. Communication between employees and superiors is going well, creating harmonious professional relationships and supporting smooth operations. In addition, the level of employee discipline is also very high, with an average lateness of only 0.35% per month.